Financial performance of Delhi Transport Corporation: a social accounting approach - Rajesh Chandra
This article analyses the performance of the Delhi Transport Corporation (DTC) in financial terms as also in the context of social and economic benefits provided by it to specific sections of population in Delhi. This is done by analysing the performance of the DTC in pure financial terms for comprehending the extent of profit and loss. Subsequently, the article analysis the performance of the DTC on the basis of social accounting for gaining insight into the financial loss arising out of providing socio-economic benefits to a segement of Delhi's population
Keywords: Finance; Delhi Transport Corporation; Local Transportation - India - Delhi